Optimization of inductively coupled plasma dry etching for planar waveguide fabrication / Lim Weng Hong - Lim, Weng Hong (2010)
Optimization of the Inductively Coupled Plasma (ICP) dry etching process parameters has been carried out. Seven main etching characteristics were considered in order to produce good etching quality. These characteristics are glass etching rates, selectivity of chromium to glass etching rate, channel side wall roughness, channel side wall vertical profile, channel cleanliness, critical dimension and resolution. Several ICP parameters that are affecting the etching characteristic were optimized in this work. These optimised ICP parameters obtained from this work are ICP power (880 W), bias power (45 W), operating chamber pressure (10 mtorr), reactant gas composition, reactant gas flow rate (35sccm of C2F6 and 9sccm of H2), and working distance (5 cm from reference point).Following the above, the dry etching process showed significant improvement from the original etching process. The etching rate was increased to 255nm/min (equivalent to 13%improvement) with selectivity of 45 (equivalent to 80% increment). Moreover, there are clear improvements in cleanliness and no polymerization was observed as compared to non-optimised samples. Furthermore, comparison between Scaning Elelctro Microscope(SEM) images of the etched surface before and after the optimization process, showing major improvements in the reduction of plasma induced surface damage also know as pin hold effect.